Influence of infecion by cestodes on biochemical parameters of thick-billed murre (Uria lomvia) and common murre (U.aalge) of the Barents Sea - M. M. Kuklina (Российский паразитологический журнал, 2016)
The comparative analysis of biochemical parameters at thick-billed murre (Uria lomvia) and common murre (U. aalge) infected by cestodes Alcataenia armillaris (Cestoda: Dilepididae) and noninfected was carried out. Negative impact of tape-worms A. armillaris on a metabolism in an organism of thick-billed and common murres was shown. It was established that concentrations of total lipids, triglycerides and glucose in plasma of blood were decreased. Also activity of the lactatdegidrigenase was increased in plasma of blood of infected birds.